Agreement Between Tele- and Face-to-Face Assessment of Neuromotor Development in High-Risk Children - Ana Isabel Rubio-López; Marie Carmen Valenza; Julia Raya-Benítez; Geraldine Valenza-Peña; Irene Cabrera-Martos; Laura López-López; Ángela Benítez-Feliponi (Applied Sciences)
Background: Early interventions in high-risk children seek to improve prognosis, minimize developmental delays, and prevent functional deterioration. The objective of this study was to evaluate the level of agreement between the face-to-face assessment and tele-assessment of neuromotor development in high-risk children between 0 and 18 months of age. Methods: Forty-five children at high risk of developmental delays were included in this study (33% female, mean gestational age of 35.31 ± 4.03 weeks). The patients were included in a face-to-face and a tele-assessment using the Alberta Infant Motor Scale (AIMS) and the level of motor evolution (Niveaux d’Évolution Motrice, NEM) assessments. Results: The analysis showed excellent interrater reliability (ρ ≥ 0.99) for the AIMS. The NEM assessment showed almost perfect reliability (kappa ≥ 0.81) for most items. Seven of them showed substantial reliability (kappa = 0.61–0.80), one moderate reliability (kappa = 0.568), and one fair reliability (kappa = 0.338). Conclusions: This study reveals an excellent/substantial interrater reliability for most of the items assessed. The results are promising to increase the accessibility to a clinical diagnosis and a rehabilitation approach to minimize the development of neuromotor delays in children at high risk.